Prosochit®-based nanoparticulate system of insulin for oral delivery: design, formulation, and characterization - Emmanuel O. Olorunsola, Koofreh G. Davies, Koton P. Ibiang, Patience C. Esukpa, Ezinne G. Uwaechi, Fakhrul Ahsan (Journal of Applied Pharmaceutical Science, 2023)
Oral delivery is a promising mechanism for improving adherence to insulin therapy in diabetes management. This work was aimed at preparing and characterizing Prosochit®-based nanoparticles of insulin for oral administration. Insulin-loaded nanoparticles were formulated by the water-in-oil-in-water double emulsion-freeze drying method using three types of Prosochit®, Prosopis gum (PRG), and chitosan (CTS) separately as emulsifiers for the outer emulsion. The formulations were analyzed for particle size, drug release, and permeation. Particle sizes of the Prosochit®-based formulations were found to be 10.40–13.85 nm (for the inner emulsion) and 128.00–160.40 nm (for the outer emulsion). Prosochit® limited the drug release at the gastric pH to a maximum of 10.1%. The maximum values of drug release in phosphate buffer pH 6.8 were 66.2%, 61.5%, 65.3%, 61.3%, and 58.2% while the permeation values were 49.8%, 53.8%, 49.1%, 54.9%, and 57.6% for the formulations containing PRG, Prosochit® 201, Prosochit® 101, Prosochit® 102, and CTS, respectively. The three types of Prosochit®-based nanoparticles have comparable controlled release and permeation properties and are superior to PRG -based and CTS -based nanoparticles for oral delivery of insulin.